Induced pluripotent stem cells as a potential therapeutic source for corneal epithelial stem cells - Zhu, Jie (Int J Ophthalmol, 2018)
Corneal blindness caused by limbal stem cell deficiency (LSCD) is one of the most common debilitating eye disorders. Thus far, the most effective treatment for LSCD is corneal transplantation, which is often hindered by the shortage of donors. Pluripotent stem cell technology including embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) have opened new avenues for treating this disease. iPSCs-derived corneal epithelial cells provide an autologous and unlimited source of cells for the treatment of LSCD. On the other hand, iPSCs of LSCD patients can be used for iPSCs-corneal disease model and new drug discovery. However, prior to clinical trial, the efficacy and safety of these cells in patients with LSCD should be proved. Here we focused on the current status of iPSCs-derived corneal epithelial cells used for cell therapy as well as for corneal disease modeling. The challenges and potential of iPSCs-derived corneal epithelial cells as a choice for clinical treatment in corneal disease were also discussed.